Effects of biochar on plant growth and hydro-chemical properties of recycled concrete aggregate - Guo, Haowen; Zhang, Qi; Chen, Yanbo; Lu, Hu (The Science of the total environment, 2023)
Biochar has been used as a sustainable amendment to mitigate environmental risks, improve plant growth and soil properties. This study conducted laboratory column tests to investigate the effects of plant-biochar interactions on shrub growth, hydraulic properties and nutrient contents of recycled concrete aggregates (RCAs). In total, three test conditions, namely, vegetated RCA without biochar (R), with 5 % biochar (R5) and 10 % biochar (R10) were subject to drying. With biochar application, total N, P and K of RCA increased by >100 %, 200 % and 31 %, respectively, while pH reduced to 8.3. With shrub growth, the lowest RCA pH was reduced to 7.8. The leaf area index (LAI) of shrub increased by 51 % due to biochar amendment, while the differences in shoot height were insignificant. The water retention capacity of RCA was enhanced by improving the saturated water content and air-entry value by 27 % and 100 %. The slope of the soil suction-LAI correlation for biochar amend cases was 1.6 times lower than R. This indicates that biochar may limit the increase of matric suction and prevent excessive water loss during drying. However, the differences between R5 and R10 were not significant. Therefore, 5 % biochar amendment is highly suggested as it can substantially improve plant growth and soil hydraulic properties during drying. [Display omitted] •Peanut shell biochar content improved total N, P and K and reduced RCA pH.•Shrub LAI and water retention capacity were enhanced due to biochar.•Peanut shell biochar may decrease excessive water loss from RCA due to ET.•5 % biochar amendment is suggested for the application.